Implementasi Program Pengembangan Kampung Keluarga Berencana (Kampong KB) di Desa Halong Kota Ambon - Tentua, Nicolin; Abidin Rengifurwarin, Zainal; Pattimukay, Hengky (Jurnal Ilmiah Global Education, 2024)
This research was a qualitative descriptive study with aims to explore facts regarding the implementation of the development of family planning villages in Halong village, Baguala district, Ambon City.This research conducted at the Population of Family Planning Agency and people belonging to couples of childbearing age in Halong village. The data collected through interviews, observation and documentation of some informants who were directly involved in the implementation process of the Family Planning Village program in Halong village, Baguala district. The data collected has processed and analyzed using qualitative descriptive analysis techniques. The results of the data analysis showed that, in general, the implementation of the Family Planning Village program in Halong village was going well. Thus it can be seen from several programs that have been running, including the elderly integrated healthcare center and data house.